Changing perspectives on the biogeography of the tropical South Pacific: influences of dispersal, vicariance and extinction - Keppel, Gunnar; Lowe, A.; Possingham, H. (Blackwell Publishing, 2009)
Aim: The biogeographical patterns and drivers of diversity on oceanic islands in the tropical South Pacific (TSP) are synthesized. We use published studies to determine present patterns of diversity on TSP islands, the likely sources of the biota on these islands and how the islands were colonized. We also investigate the effect of extinctions. Location: We focus on oceanic islands in the TSP. Methods: We review available literature and published molecular studies. Results: Examples of typical island features (e.g. gigantism, flightlessness, genderdimorphism) are common, as are adaptive radiations. Diversity decreases with increasing isolation from mainland sources and with decreasing size and age of archipelagos, corresponding well with island biogeographical expectations. Molecular studies support New Guinea/Malesia, New Caledonia and Australia as major source areas for the Pacific biota. Numerous studies support dispersalbased scenarios, either over several 100 km (long-distance dispersal) or over shorter distances by island-hopping (stepping stones) and transport by human means (hitch-hiking). Only one vicariance explanation, the eastward drift of continental fragments (shuttles) that may have contributed biota to Fiji from New Caledonia, is supported by some geological evidence, although there is noevidence for the transport of taxa on shuttle fragments. Another vicariance explanation, the existence of a major continental landmass in the Pacific within the last 100 Myr (Atlantis theory), receives little support and appears unlikely. Extinction of lineages in source areas and persistence in the TSP has probably occurred many times and has resulted in misinterpretation of biogeographical data. Main conclusions: Malesia has long been considered the major source region for the biota of oceanic islands in the TSP because of shared taxa and high speciesdiversity. However, recent molecular studies have produced compelling support for New Caledonia and Australia as alternative important source areas. They also show dispersal events, and not vicariance, to have been the major contributors to the current biota of the TSP. Past extinction events can obscure interpretations of diversity patterns.